Program Evaluation of a Workshop on Prairie Strips for Farm Advisors: Framing the Co-Occurring Outcomes of Low Knowledge Acquisition and High Confidence - Rachael Whitehair; Nancy Grudens-Schuck; Lisa A. Schulte (Horticulturae, 2022)
The agricultural conservation practice of prairie strips is new and novel. Prairie strips planted in row crop fields warrants greater adoption because the application decreases erosion; protects water quality; and supports habitat for wildlife and biodiversity, including pollinators. Prairie strips are a vegetative practice composed of diverse, native, and mostly perennial species that, as a community, follow principles of ecological succession; however, they must be managed for success. Farm advisor comprehension of practice characteristics is key for adoption by producers and landowners. This article reports on a developmental evaluation of workshops intended to change farm advisor knowledge, skills, and confidence related to prairie strips management for use in consulting with farmers and landowners. The study used pre-post instruments of knowledge and skill focused on prairie species identification and age of prairie strips planing; pre-then post-end of session questions were asked in a survey to report change in knowledge, skill, and confidence, as well as farm advisor situation. Advisors reported increased confidence, but acquisition of prairie knowledge and skills resulted in flat to lower scores. The paper explores the discrepancy of lower cognitive scores (knowledge and skills) compared to higher confidence. Explanations explore the phenomena of satisficing and perceived self-efficacy to explain the differential.